40Ar/39Ar age constraints for an early Alpine metamorphism of the Sakar unit, Sakar–Strandzha zone, Bulgaria. (14th December 2020) - Bonev, Nikolay; Spikings, Richard; Moritz, Robert
Abstract: We investigated the Sakar unit metamorphic rocks of the Sakar–Strandzha zone in Bulgaria, using 40 Ar/ 39 Ar dating of amphibole from the polymetamorphic basement and white mica in the overlying upper Permian metasedimentary rocks of the Paleokastro Formation. The amphibole and white mica revealed plateau ages of 140.50 ± 1.75 Ma and 126.19 ± 1.29 Ma, respectively, indicating an Early Cretaceous cooling history of the regional amphibolite-facies metamorphism to greenschist-facies conditions. Similar metamorphic grades and cooling histories of the Sakar unit share evidence with the nearby Rhodope Massif for the northern Aegean region-wide early Alpine tectonometamorphic event.